Preparation and application of elemental copper nanoparticle loaded s-Ti3C2Tx nanosheet composite material

By loading copper nanoparticles on a single-layer Ti3C2Tx nanosheet, Cu@s-Ti3C2Tx composite material is formed, and the problem of low reactivity of multi-layer Ti3C2Tx materials is solved, and high sensitivity detection of dopamine is achieved, with a wide linear range and a low detection limit.

CN119588386APending Publication Date: 2025-03-11HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411348903.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-03-11

Smart Images

  • Figure HDA0005061766840000011
    Figure HDA0005061766840000011
  • Figure HDA0005061766840000012
    Figure HDA0005061766840000012
  • Figure HDA0005061766840000021
    Figure HDA0005061766840000021
Patent Text Reader

Abstract

The invention relates to preparation and application of a Cu (at) s-Ti3C2Tx composite material. The composite material obtained by the invention is used for analyzing and detecting dopamine by an electrochemical method. The invention designs and prepares an elemental copper nanoparticle loaded thin-layer Ti3C2Tx nanosheet composite material (Cu (at) s-Ti3C2Tx), a LiF / HCl etching method is utilized to prepare multiple layers of Ti3C2Tx, an ultrasonic stripping method is utilized to prepare thin-layer Ti3C2Tx nanosheets (s-Ti3C2Tx), and finally, copper nanoparticles are grown on the s-Ti3C2Tx in situ to form the Cu (at) s-Ti3C2Tx composite material. The s-Ti3C2Tx has a larger effective surface area, and due to the good catalytic activity of the copper nanoparticles and the synergistic effect of the copper nanoparticles and the s-Ti3C2Tx, the Cu (at) s-Ti3C2Tx composite material has excellent electrocatalytic activity. The prepared material has a wide linear range (0.8-150 [mu] M), a low detection limit (0.267 [mu] M) and a high specific surface area (2.16 cm < 2 >) on dopamine detection. The preparation process is simple and convenient, the cost is low, and the obtained material has good electrochemical sensing performance on dopamine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical sensors, and in particular to a Cu@s-Ti 3 C 2 T x Preparation and application of composite materials. Background Art

[0002] Dopamine (DA) is an important neurotransmitter in the human body and plays a very important role in the information transmission of the central nervous system and cardiovascular system. Abnormal dopamine concentration in the human body can lead to neurological diseases such as addictive behavior, schizophrenia, Parkinson's syndrome, etc. Therefore, the accurate detection of dopamine concentration has important biomedical value. At present, there are many methods for detecting small biological molecules such as dopamine, mainly including high performance liquid chromatography, ultraviolet-spectrophotometry, high performance capillary electrophoresis, fluorescence and electrochemical analysis. Among them, electrochemical analysis is widely used due to its advantages such as simple operation, cheap equipment, high sensitivity and short analysis time.

[0003] Since 2011, MXene, a new type of two-dimensional nanosheet, has attracted widespread attention. 3 C 2 T x It is one of the most widely studied materials. It has a large number of negatively charged functional groups such as -F, -OH, and -O on its surface, so it has excellent conductivity, high hydrophilicity, good physical and chemical stability, and lubricity. 3 C 2 T x The material has been applied in lithium-ion batteries, supercapacitors, photocatalysts, electrochemical sensors and other fields. 3 C 2 T x The dense structure between material layers tends to weaken its chemical properties as the thickness increases, and when the thickness is too large, it will inhibit ion diffusion. 3 C 2 T x Although the surface contains a large number of functional groups, it is difficult to expose the active groups between layers, resulting in low reaction activity. In recent years, influenced by the graphene craze, the exfoliation of layered materials to form nanometer-level flake materials has attracted more and more attention. Theoretically, the nanometer-level thickness of the flakes will give the material some special physical and chemical properties that are different from layered materials, and more surface groups will be exposed.

[0004] Given that single-layer Ti 3 C 2 T xUnique structure and physicochemical properties, excellent electrocatalytic activity and conductivity of copper nanoparticles, and excellent effect of Cu materials in the field of biosensors. The present invention uniformly loads single copper nanoparticles on a single layer of Ti 3 C 2 T x Cu@s-Ti nanosheets with excellent performance and low cost 3 C 2 T x Electrochemical sensing materials. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of multilayer Ti 3 C 2 T x As an electrochemical biosensor material with limited ion transport and low reaction activity, a single layer of Ti was prepared by liquid phase exfoliation. 3 C 2 T x Nanosheets (s-Ti 3 C 2 T x ). In s-Ti 3 C 2 T x The nanosheet substrate is loaded with single copper nanoparticles to increase the specific surface area of ​​the material. The excellent electrocatalytic activity and electrical conductivity of the copper nanoparticles also further improve the sensing performance of the composite material to dopamine. 3 C 2 T x Cu@s-Ti is formed on the nanosheet substrate 3 C 2 T x Preparation and application of composite materials.

[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0007] 1. s-Ti 3 C 2 Preparation: Add LiF and concentrated hydrochloric acid into a polytetrafluoroethylene beaker, stir to mix evenly, weigh a quantitative amount of Ti 3 AlC 2, Add it to the mixed solution in small amounts and for several times, and etch it for a certain time in a water bath. After etching, separate the product by centrifugation, wash it with dilute hydrochloric acid to remove unreacted LiF, and then wash the product with deionized water several times until the pH of the product supernatant reaches above 6. Disperse the product in deionized water and place it in N 2 Ultrasonic treatment was performed under a circulating atmosphere, and then the product was separated by centrifugation, and the supernatant was freeze-dried to obtain s-Ti3 C 2 T x。

[0008] 2. Preparation of composite materials: s-Ti 3 C 2 T x Add to anhydrous ethanol and disperse by ultrasound. 3 ) 2 ·3H 2 O was dissolved in ethylene glycol to form a solution, and Cu(NO 3 ) 2 ·3H 2 O solution was added dropwise to the s-Ti 3 C 2 T x After stirring the ethanol dispersion evenly, slowly add NaBH 4 , magnetic stirring was performed in an ice-water bath to allow the reaction to proceed fully. The product was separated by centrifugation, washed several times with anhydrous ethanol, and vacuum dried to obtain the composite material Cu@s-Ti 3 C 2 T x .

[0009] The mass of LiF described in step 1 is 1.5-1.7 g; the amount of concentrated hydrochloric acid used is 20-24 mL.

[0010] Ti described in step 1 3 AlC 2 The mass is 1-1.2g; etching is carried out at 40-45℃ for 36-48h.

[0011] The concentration of the dilute hydrochloric acid in step 1 is 1-1.2 mol / L; the number of washings with dilute hydrochloric acid is 2-4 times; and the number of washings with deionized water is 10-15 times.

[0012] The product described in step 1 is dispersed in 60-80 mL of deionized water; the ultrasonic time is 1-3 h.

[0013] s-Ti described in step 2 3 C 2 T x The mass of 30 mg was added into 20-30 mL of anhydrous ethanol.

[0014] The Cu(NO 3 ) 2 ·3H 2 The mass of O is 10-30 mg; the amount of ethylene glycol is 5 mL; NaBH 4 The mass is 2.5-7.5mg.

[0015] The solution in step 2 is stirred in an ice-water bath for 2-3 hours; washed by centrifugation with anhydrous ethanol for 2-4 times; and dried under vacuum conditions at 50-60° C. for 10-12 hours.

[0016] Compared with the prior art, the present invention has the following characteristics:

[0017] The present invention successfully loads transition metal copper nanoparticles on a single layer of Ti by in-situ reduction. 3 C 2 T x (s-Ti 3 C 2 T x ) nanosheets, preventing the multilayer Ti 3 C 2 T x The problem of low reaction activity is caused by limited ion diffusion. At the same time, the introduction of copper nanoparticles not only increases the specific surface area and conductivity of the material, but the excellent electrocatalytic activity of the copper nanoparticles themselves also improves the sensing performance of the material. While achieving low cost, a wide linear range (0.8-150μM) and a low detection limit (0.267μM) as well as a high specific surface area of ​​2.16cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Ti 3 AlC 2 、s-Ti 3 C 2 T x 、Cu@s-Ti 3 C 2 T x Powder X-ray diffraction pattern (XRD).

[0019] Figure 2 s-Ti 3 C 2 T x Transmission electron microscopy (TEM) images of the material.

[0020] Figure 3 Cu@s-Ti 3 C 2 T x Transmission electron microscopy (TEM) images of the composite materials.

[0021] Figure 4 Cu@s-Ti 3 C 2 T x X-ray photoelectron spectroscopy (XPS) of the composites.

[0022] Figure 5 For Cu@s-Ti in the concentration range of 20-100 μM 3 C 2 T x Differential pulse voltammetry (DPV) of dopamine (DA) detection.

[0023] Figure 6 For 5 mM [Fe(CN) 6 ] 3- / 4- In a mixed solution of 0.1M KCl, Cu@s-Ti 3 C 2 T x Cyclic voltammetry (CV) curves at different scan rates in the range of 10-100 mV / s.

[0024] Figure 7 For 5 mM [Fe(CN) 6 ] 3- / 4- In a mixed solution of 0.1M KCl, bare glassy carbon electrode, s-Ti 3 C 2 T x 、Cu@s-Ti 3 C 2 T x Electrochemical impedance spectroscopy (EIS).

[0025] Figure 8 Cu@s-Ti 3 C 2 T x Differential pulse voltammetry (DPV) of dopamine (DA) under continuous detection. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0027] Implementation Case 1

[0028] This implementation case is a single-layer Ti 3 C 2 T x (s-Ti 3 C 2 T x ), which is prepared according to the following method:

[0029] Add 1.6 g LiF and 20 mL concentrated hydrochloric acid into a 50 mL polytetrafluoroethylene beaker and stir for 40 min to mix them evenly. 3 AlC 2, add it to the above mixed solution in small amounts several times, and etch in a water bath for 48 hours. After etching, separate the product by centrifugation, wash it three times with 1M dilute hydrochloric acid to remove unreacted LiF, and then wash the product with deionized water until the pH of the product supernatant reaches above 6. Disperse the product in 70mL deionized water and place it in N 2 The product was separated by centrifugation under ultrasonic treatment for 2 h, and the supernatant was lyophilized to obtain s-Ti 3 C 2 T x。

[0030] Implementation Case 2

[0031] This embodiment provides a Cu@s-Ti 3 C 2 T x A composite material, prepared according to the following method:

[0032] Take 30mg s-Ti 3 C 2 T x Add 30 mL of anhydrous ethanol and disperse by ultrasonication for 30 min. 3 ) 2 Dissolve in 5 mL of ethylene glycol to form a solution, and stir vigorously to mix Cu(NO 3 ) 2 ·3H 2 O solution was added dropwise to the s-Ti 3 C 2 T x After stirring and mixing evenly, slowly add 3.4 mg NaBH 4 The mixture was stirred magnetically for 2 h in an ice-water bath to allow for full reaction. The product was separated by centrifugation, washed with anhydrous ethanol three times, and vacuum dried at 60 °C for 12 h to obtain the composite material Cu@s-Ti 3 C 2 T x .

[0033] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0034] Figure 1 Ti 3 AlC 2 、s-Ti 3 C 2 T x 、Cu@s-Ti 3 C 2 T x Powder X-ray diffraction pattern (XRD). As shown in the figure, Ti3 C 2 T x The (002) peak of the diffraction pattern of the nanosheets is similar to that of the raw material Ti 3 AlC 2 Compared with the obvious blue shift, this phenomenon indicates that Ti 3 C 2 T x The spacing between layers increases. 3 AlC 2 In comparison, Ti 3 C 2 T x The highest diffraction peak at 2θ≈39° of the nanosheets disappears, indicating that the Ti 3 AlC 2 The Al element in the raw material is effectively etched away. The lack of Cu nanoparticle diffraction peaks is due to the low content of copper nanoparticles. However, due to the doping of copper nanoparticles, Cu@s-Ti 3 C 2 T x The diffraction peaks at 2θ≈5° and 61° are relative to s-Ti 3 C 2 T x The widening also shows that Cu@s-Ti 3 C 2 T x Successful preparation.

[0035] Figure 2 Shown is s-Ti 3 C 2 T x Transmission electron microscopy (TEM) of the material shows that a single layer of Ti was successfully prepared. 3 C 2 T x (s-Ti 3 C 2 T x ), and has high dispersibility, with an average diameter of approximately 300-500nm.

[0036] Figure 3 Cu@s-Ti 3 C 2 T x Transmission electron microscopy (TEM) images of the composite material show that single copper nanoparticles are widely distributed in the s-Ti 3 C 2 T x Nanosheet substrate.

[0037] Figure 4 Cu@s-Ti 3 C2 T x X-ray photoelectron spectroscopy (XPS) of the composite material. As shown in the figure, a) is Cu@s-Ti 3 C 2 T x The XPS spectrum of Cu@s-Ti 3 C 2 T x There are elements Cu, Ti, C, O, and F. Among them, the O element is due to s-Ti 3 C 2 T x The oxygen-containing functional groups on the basal surface and the slight oxidation of the surface exist, and the F element is caused by the intercalation of the F group during the etching process. b) Figure is the XPS energy spectrum of the C element under the 1s orbital, which can be fitted into 4 characteristic peaks, with binding energies of 288.15ev, 285.5ev, 284.4ev and 281.54ev corresponding to CF, CO, CC and C-Ti bonds respectively. This proves that s-Ti 3 C 2 T x There are -O, -F and other groups on the surface. Figure c) is the XPS spectrum of the O element in the 1s orbital. After peak fitting, four characteristic peaks are formed. The binding energies are 532.4ev, 531.2ev, 530.1ev, and 529.5ev, corresponding to C-Ti-(OH) respectively. x 、C-Ti-O x , Cu-O, and Ti-O bonds, and the copper nanoparticles are slightly oxidized. d) Figure 4 is the XPS spectrum of the Cu element in the 2p orbital. After peak fitting, four characteristic peaks are formed, among which Cu 2p 3 / 2 Orbitals and 2p 1 / 2 The characteristic peaks at 9321ev and 951.95ev respectively prove the presence of Cu in the material. 0 The characteristic peaks at 934.3ev and 954.1ev indicate the presence of low-valent copper in the material, which proves the successful loading of elemental copper nanoparticles and corresponds to the origin of the Cu-O bond in Figure c) above.

[0038] Figure 5 Shown is the concentration range of Cu@s-Ti in 0.1 M PBS buffer at 20-100 μM. 3 C 2 T x Differential pulse voltammetry (DPV) curve for detecting dopamine (DA). As can be seen from the figure, within the concentration range of 20-100 μM, with the gradual addition of equal concentrations of DA, the oxidation peak current gradually increases and is linearly related to the DA concentration (see Figure b), which indicates that Cu@s-Ti 3 C 2T x It has good electrocatalytic activity towards DA.

[0039] Figure 6 Shown are 5 mM [Fe(CN) 6 ] 3- / 4- In a mixed solution of 0.1M KCl, Cu@s-Ti 3 C 2 T x Cyclic voltammetry (CV) curves at different scan rates in the range of 10-100 mV / s. According to the Randles-Sevick equation I p =2.69×10 5 n 3 / 2 A eff D 0 1 / 2 CV 1 / 2 , where V 1 / 2 , C, D 0 , A eff , n, I p represent the square root of scan rate, solution concentration, [Fe(CN) 6 ] 3- / 4- The diffusion coefficient, active surface area, number of electron transfers and anodic peak current of 0 =7.6×10 -6 cm 2 / s. From Figure b), it can be concluded that the linear relationship between the anode peak current and the square root of the scan rate is I p =11.9187v 1 / 2 -23.0534(R 2 =0.987), substituting into the above Randles-Sevick equation to obtain A eff ≈2.16cm 2 , much larger than the glassy carbon electrode (0.0707 cm 2 .

[0040] Figure 7 Shown are 5 mM [Fe(CN) 6 ] 3- / 4- In a mixed solution of 0.1M KCl, bare glassy carbon electrode, s-Ti 3 C 2 T x 、Cu@s-Ti 3 C 2 T x Electrochemical impedance spectroscopy (EIS). The semicircle in the high-frequency region of the graph represents the electron transfer resistance (R ct ): The smaller the diameter, the smaller the resistance and the faster the electron transfer rate. It can be seen from the figure that Cu@s-Ti 3C 2 T x R ct 160Ω, much smaller than s-Ti 3 C 2 T x , R of glassy carbon electrode ct .

[0041] Figure 8 Cu@s-Ti 3 C 2 T x The differential pulse voltammetry (DPV) of dopamine (DA) was continuously monitored. As shown in Figure a), the response current of DA showed a uniform increase as the concentration of DA continued to accumulate (see Figure b). After calculation, the concentration range of linear growth was 0.8-150μM, and the detection limit was 0.267μM (3S / N), where S is the standard deviation of three consecutive measurements of the blank sample, and N is the slope of the fitting curve in Figure b.

[0042] In summary, the copper nanoparticles in Example 2 are loaded on a single layer of Ti 3 C 2 T x Cu@s-Ti is formed on the nanosheet substrate 3 C 2 T x The composite material was successfully synthesized by an in-situ reduction synthesis method and was successfully prepared into an electrochemical sensing electrode for detecting DA concentration. 3 C 2 T x The preparation of multilayer Ti 3 C 2 T x The ion transfer rate is limited, resulting in low reaction activity. 3 C 2 T x It also has a larger active surface area, which can expose more surface sites than multilayer Ti 3 C 2 T x It has the advantages of greater negative potential and easier compounding. The introduction of copper nanoparticles not only enhances the electrocatalytic ability of the material, but also increases the active surface area of ​​the material and promotes the electron transfer ability. The material has good electrocatalytic activity and conductivity, and has good electrochemical sensing performance in DA concentration detection.

Claims

1. A single copper nanoparticle loaded with s-Ti3C2T x Cu@s-Ti3C2T is formed on the nanosheet substrate x The preparation process of the composite material is characterized by: (1) s-Ti3C2T x Preparation: Add LiF and concentrated hydrochloric acid into a polytetrafluoroethylene beaker, stir to mix evenly, weigh a quantitative amount of Ti3AlC 2, Add it into the above mixed solution in small amounts and for multiple times, and etch it for a certain period of time in a water bath. After etching, the product was separated by centrifugation. It was first washed with dilute hydrochloric acid to remove unreacted LiF, and then washed with deionized water for multiple times until the pH of the product supernatant reached above 6. The product was dispersed in deionized water and ultrasonically treated under a N2 flow atmosphere. The product was then separated by centrifugation, and the supernatant was freeze-dried to obtain s-Ti3C2T x。 (2) Preparation of composite materials: s-Ti3C2T x Add it to anhydrous ethanol and disperse it by ultrasound. Dissolve Cu(NO3)2·3H2O in ethylene glycol to form a solution. Add the Cu(NO3)2·3H2O solution dropwise to the s-Ti3C2T x After stirring and mixing evenly in the ethanol dispersion, NaBH4 was slowly added and magnetically stirred in an ice-water bath to allow for full reaction. The product was separated by centrifugation, washed several times with anhydrous ethanol, and vacuum dried to obtain the composite material Cu@s-Ti3C2T x .

2. According to claim 1, the mass of LiF described in step (1) is 1.5-1.7 g; the amount of concentrated hydrochloric acid used is 20-24 mL.

3. According to claim 1, the mass of Ti3AlC2 described in step (1) is 1-1.2 g; etching is carried out at 40-45°C for 36-48 hours.

4. According to claim 1, the concentration of the dilute hydrochloric acid in step (1) is 1-1.2 mol / L; the number of washings with dilute hydrochloric acid is 2-4 times; and the number of washings with deionized water is 10-15 times.

5. According to step (1) of claim 1, the product is dispersed in 60-80 mL of deionized water; the ultrasonic separation time is 1-3 h.

6. The s-Ti3C2T3 according to step (2) of claim 1 x The mass of is 30 mg, add it Add to 20-30 mL of anhydrous ethanol.

7. According to step (2) of claim 1, the mass of Cu(NO3)2·3H2O is 10-30 mg; the amount of ethylene glycol is 5 mL; and the mass of NaBH4 is 2.5-6 mg.

8. The solution according to step (2) of claim 1 is stirred in an ice-water bath for 2-3 h; washed by centrifugation with anhydrous ethanol for 2-4 times; and dried under vacuum conditions at 50-60° C. for 10-12 h.

9. Cu@s-Ti3C2T prepared by the method for preparing the composite material according to claims 1 to 8 x Applied to the electrochemical analysis and detection of dopamine (DA).